Comparing the quality of life for boarders and day students at the regional boarding schools in Giresun-Turkey/Giresun İlinde yatılı bölge okullarında okuyan yatılı ve gündüzlü öğrencilerin yaşam kalitelerinin karşılaştırılması - Emine Küçük; Osman Günay (Turkish Society of Public Health Specialists, 2014)
Abstract Objective: Regional boarding schools have been established to provide primary education in the sparsely populated areas in Turkey. Boarders and day-students study together in these schools. This study was carried out to compare the quality of life of boarders and day-students the regional boarding schools. Methods: A total of 1126 students, 634 boarders and 492 day- students, at the 4th-8th grades of nine boarding schools in Giresun province of Turkey participated in this study. A socio-demographic questionnaire and a Pediatric Quality of Life Inventory were filled by the students. The Chi square test, unpaired t test, generalized linear model (GLM), and Pearson simple correlation were used for the statistical analyses. Results: It was found that the life quality scores of the boarders were lower than those of the day- students for all dimensions of the Pediatric Quality of Life inventory (p<0.05). Life quality scores of the female students were found to be lower than those of the males (p<0.05). There were positive correlations between the age and life quality scores of the boarders. Conclusions: The Life quality scores of the boarders were lower than that of the day-students. Life quality scores of the girl boarders were much lower. More attention should be given to the living conditions of the boarders in order to improve their life quality levels. Key Words: Student, life style, quality of life Özet Amaç: Türkiye'de nüfusun dağınık olduğu bölgelerde, temel eğitimi sağlamak amacıyla yatılı ilköğretim bölge okulları açılmıştır. Bu okullarda yatılı ve gündüzlü öğrenciler birlikte okumaktadır. Bu araştırma yatılı bölge okullarında yatılı ve gündüzlü olarak okuyan öğrencilerin yaşam kalitesi düzeylerini karşılaştırmak amacıyla yapılmıştır. Yöntem: Giresun ilindeki dokuz yatılı bölge okulunun 4-8. sınıflarında okuyan, 634'ü yatılı, 492'si gündüzlü olmak üzere toplam 1126 öğrenci araştırma kapsamına alındı. Öğrenciler tarafından, sosyo-demografik anket ve Pediatrik Yaşam Kalitesi Ölçeği dolduruldu. Verilerin istatistiksel analizinde ki kare testi, unpaired t testi, genel lineer model (GLM) ve Pearson simple korelasyon analizi kullanıldı. Bulgular: Yatılı öğrencilerde, Pediatrik Yaşam Kalitesi Ölçeği'nin bütün boyutlarında ortalama puanlar gündüzlü öğrencilerden daha düşük bulundu (p<0.05). Her iki grupta, kız öğrencilerin yaşam kalitesi puanları erkek öğrencilerden daha düşük bulundu (p<0.05). Yatılı öğrencilerde, yaş ile yaşam kalitesi puanları arasında pozitif yönde ilişkiler bulundu.Sonuç: Yatılı öğrencilerin yaşam kalitesi puanları gündüzlü öğrencilerden düşüktür. Yatılı kız öğrencilerin yaşam kalitesi puanları daha da düşüktür. Yatılı öğrencilerin yaşam kalitesi düzeyini yükseltmek için, yaşam koşullarının iyileştirilmesi yönünde çaba harcanmalıdır. Anahtar Kelimeler: Öğrenciler, yaşam biçimi, yaşam kalitesi